"Biting the hand that feeds them? The case of Ghanaian Pentecostal discourse on 'breaking from the past'". Issue 1 (2nd January 2021) - Tweneboah, Seth
ABSTRACT: Ghanaian Pentecostal pastor-prophets encourage their members to break away from the ancestral past which is projected as a vessel of demonic operations responsible for mishaps in society. Yet traditional priestly actors have challenged the notion that indigenous religious imaginations and ritual spaces are a crucial platform where power and recognition are contested by some pastor-prophets. As such, these traditional priests have particularly warned pastor-prophets to desist from oppugning traditional religion or face exposure of their underground dealings with the traditionalists. In this paper, I reflect on confrontations between traditional priestly actors and neo-Pentecostal pastor-prophets in Ghana, arguing that such confrontations are a function of a power struggle as to who the 'Big Men' are in contemporary Ghanaian society. To understanding these confrontations, I contend further that there is the need to interrogate the differing points of continuity and disjuncture between these two traditions.